Islamic Religiosity as a Control of Suicide Intent among Final-Year Students through Spiritual Experience - Iredho Fani Reza; Kiki Cahaya Setiawan; Eko Oktapiya Hadinata; Shams, Fariza MD (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research investigates the impact of Islamic religiosity and spiritual experiences on suicide intent among final-year students. The phenomenon of final-year students experiencing difficulties in completing their final assignments and even resorting to suicide serves as the background for this study. The research methodology employed is quantitative with a survey approach. Data analysis was conducted using path analysis techniques through Mplus version 8.0 software and its supporting tool, IBM SPSS version 24. The study's population consisted of final-year students at Sriwijaya University and Raden Fatah State Islamic University, Palembang. The sample was selected using a multistage sampling technique, with 412 respondents. This study used research instruments, including the Harkavy Asnis Suicide Scale (HASS) by Jill M. Harkavy Friedman, the Islamic Religiosity Scale by Hisham Abu Raiya et al., and the Daily Spiritual Experience Scale by Lynn G. Underwood. The research results indicate that Islamic religiosity has a significant influence on suicide intent through spiritual experiences as a mediator. Spiritual experiences are associated with a reduction in suicide intent, and both factors contribute to reducing suicide intent among students (R Square Change = 12%). Additionally, there is also a direct influence of Islamic religiosity on suicide intent without mediation. Similar findings apply to spiritual experiences. Recommendations from this research include encouraging students to engage in religious practices, strengthening spiritual experiences, and maintaining a balance between academic and religious aspects. The importance of mental health support and suicide prevention programs within the campus environment is also emphasized.